HINDU WOMAN IN THE HOLY SCRIPTURES, AN ANTHROPOLOGY OF RELIGION APPROACH - I Nyoman Yoga Segara; I Nyoman Subagia; I Gede Suwantana; I Made Adi Brahman (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
The background of this research takes a different position with many writings discussing Hindu women who are generally said to be marginal and alienated from their cultural structure and social system. Even if it is associated with customs and culture, one of them is through the patrilineal system as it applies in Bali, they are considered to have no contribution at all. Another theme that is also often found in many types of research is the ambivalent attitude that worships Hindu women while at the same time degrading them, especially concerning women's bodies. There are not many writers who re-discuss this theme from the anthropology of religion or religious anthropology which views women in the scriptures not only as a theological and divine dimension but also as an open space for how women can see themselves and act in their culture. Through qualitative research methods using the perspective of religious anthropology based primarily on Hindu scriptures, this study found in-depth interviews and participatory observations and anthropological perspectives of religion enriched with literature studies in the form of holy scriptures, this study found so many important roles of Hindu women who not many people know. The negative stigma about women, the natural-cultural dichotomy, and those who consider Hindu women to be sub-ordinate can only be enlightened through this research.